Universal Architecture Study on The Redesign of Marsudi Putra 2 Pandak Special School - Nurina Vidya Ayuningtyas; Fitrian Nur Hidayatullah; Kindi (Program Studi Arsitektur, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2025)
Sekolah Luar Biasa (SLB) are schools that are intended for children with special needs so that they can obtain basic education services. SLB Marsudi Putra 2 Pandak was chosen as the object of research because this school has shortcomings in terms of building facilities and infrastructure due to inefficient room layout. The purpose of this study is to examine the universal architectural approach to SLB Marsudi Putra 2 Pandak so that an evaluation can be carried out so that SLB Marsudi Putra 2 Pandak meets the standards for universal design. The research method used is a precedent study and qualitative approach, namely by taking precedents from several SLB buildings through direct observation, interviews with users, and documentation studies related to the building. The results of this study are that SLB Marsudi Putra 2 Pandak has not met the building standards for universal architectural design, so a design proposal was submitted for this building which was able to show that the application of universal architecture can provide design concept results that accommodate the comfort and needs of students with special needs and provide an effective basic concept in terms of space, room shape, lighting system, measurement, and comfortable room elements for people with special needs.